Combination of submicroemulsion and phospholipid complex for novel delivery of ursodeoxycholic acid. (May 2014) - Ma, Yue-Qin; Li, Gang; Xu, Jiang-Hong; Zhang, Jing; Zhang, Zeng-Zhu; Xiao, Han-Yang; Li, Xian-Fei
Abstract The objective of this study was to prepare and characterize ursodeoxycholic acid submicron emulsion (UA-SME) loaded with ursodeoxycholic acid phytosomes (UA-PS) and optimize the process variables. A screening experiment with response surface methodology with Box-Behnken design (BBD) was used to optimize the process parameters of UA-SME. The blood concentrations of UA after oral administration of UA-SME and UA coarse drug were assayed. The optimum process conditions were finally obtained by using a desirability function. It was found that stirring velocity, homogenization pressure and homogenization cycles were the most important variables that affected the particles size, polydispersity index and entrapment efficiency of UA-SME. Results showed that the optimum stirring velocity, homogenization pressure and cycles were 16 000 rpm, 60 MPa and 10 cycles, respectively. The mean diameter, polydispersity index and entrapment efficiency of UA-SME were 251.9 nm, 0.241 and 74.36%, respectively. Pharmacokinetic parameters of UA and UA-SME in rats were Tmax 2.215 and 1.489 h, Cmax 0.0364 and 0.1562 μg/mL, AUC0–∞ 3.682 and 13.756 μg h/mL, respectively. The bioavailability of UA in rats was significantly different (p < 0.05) after oral administration of UA-SME compared to those of UA coarse drug. This was due to improvement of the hydrophilicity and lipophilic property of UA-SME.